239 The Role of Rapid Qualitative Immunochromatographic Antibody Test for Screening of Coeliac Disease in Children. (11th October 2021) - Mašić, Mario; Musil, Vera; Petričević-Vidović, Tanja; Sičaja, Enida; Hojsak, Iva; Jadrešin, Oleg; Kolaček, Sanja; Mišak, Zrinjka
Abstract : Coeliac disease (CD) is an immune-mediated inflammatory disease triggered by dietary gluten and related proteins in genetically predisposed individuals. Standard serology testing and small bowel biopsy are used to establish the diagnosis of CD. New and improved point-of-care (POC) methods are non-invasive and could help reduce the diagnostic delay of CD. We aimed to determine the prevalence (using rapid POC test) and clinical characteristics of CD found by screening in first-grade schoolchildren. A rapid qualitative immunoassay POC test (Simtomax Blood Drop DGP) designed for detection of immunoglobulin (Ig) A and IgG deamidated gliadin antibodies (DGP) as well as total IgA (to identify IgA deficient patients) in whole blood was used to test healthy, first-grade schoolchildren who consumed gluten regularly without restrictions. All children with positive POC test were examined by paediatric gastroenterologist and referred to do total IgA and coeliac serology testing – IgA antibodies against type-2 tissue transglutaminase (tTG) in IgA sufficient children and IgG DGP in those with IgA deficiency. Finally, the diagnosis of CD was established according to diagnostic guidelines of European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN). Out of 1404 children (51% female, mean age 7.23 y) tested, 85 (6.05%) had positive rapid POC test. All those were referred to do serology testing but 2 were excluded from the analysis as were older than first-graders and 4 refused. Out of 79 tested, 8 had positive IgA tTG (6 with values of more than 10x upper limit of normal (ULN)). Finally, 7 children were diagnosed with CD (0.5%): one with no-biopsy approach according to ESPGHAN guidelines and 6 with positive biopsies (one had Marsh 2 and 5 Marsh 3). One child (tTG was 4x ULN) had normal biopsy and CD was not confirmed. There was no significant difference in children with CD and the children with negative serology in age (median 7.08 vs 7.25 years, P>0.05), BMI (median 16.39 vs 15.36, p>0.05), presence of symptoms (57% vs 44%, p>0.05) nor in positive family history for CD (none vs one). Children diagnosed with CD did not have significantly more symptoms nor lower BMI, and could not have otherwise been diagnosed clinically. In our study, the prevalence of CD in first-grade children was overall 0.5%. This is higher prevalence of CD than reported earlier for Croatia, showing the benefit of IgA and IgG DGP based POC test in screening.